Uncovering the link between environmental factors and coral immunity: A study of fluorescent protein expression and phenoloxidase activity in Acropora cervicornis - Toledo-Hernández, Carlos; Ruiz-Diaz, Claudia Patricia; Ramírez-Lugo, Juan Sebastian; Torres-Díaz, Marielys; Santiago-Pagán, Lisby; Bruno-Chardón, Andrea; Díaz-Vázquez, Liz M. (Frontiers in Marine Science, 2023)
Worsening environmental conditions due to climate change have profoundly affected the health of coral reefs worldwide. Thus, understanding how corals respond to fluctuating and/or extreme levels of temperature and solar irradiation will guide future protection and restoration efforts of this valuable ecosystem. Herein, we present a study of the immune responses of the endangered coral Acropora cervicornis to seasonal fluctuations in water temperature (WT), light intensity (LI), and water depth. Immune responses were observed by measuring the concentration of green and cyan fluorescent proteins (GFP and CyFP) and the activity of phenoloxidase (PO), an enzyme involved in the biosynthesis of the photoprotective protein melanin. To study these responses, visually healthy A. cervicornis fragments were placed at 8, and 12 m depth, and GFP, CyPF, and PO activity were measured at three-month intervals over a 12-month period. Seawater temperature and light intensity were also measured at each depth during this period. A general linear mixed model was used to determine the effects of seasonal variations of WT, LI, and water depth on the immune proteins. GFP, CyFP, and PO activity varied significantly across time – all higher in late summer/early fall and lower in late winter/early spring. Likewise, WT and LI significantly affected GFP, CyFP, and PO activity. On the other hand, water depth only had a significant effect on fluorescent protein concentrations but not PO activity. Our study demonstrates that corals can modulate these key immune-related proteins throughout natural seasonal fluctuations. That is, increasing in months of higher thermal and light conditions while decreasing in months with mild thermal and light conditions. The phenotypic plasticity of A. cervicornis in adapting to a changing environment underscores the importance that in future studies time of the year should be a meaningful consideration when evaluating the responses of A. cervicornis to the environment.